Michel Foucault y la estructura trágica. Una temprana lectura nietzscheana de la tragedia - Abeijón, Matías (2018)
“Michel Foucault and the Tragic Structure. An Early Nietzschean Reading of Tragedy”. The purpose of this article is to investigate the statute of the tragic in Michel Foucault’s early texts, especially in the original preface of Histoire de la folie à l’age classique. It will be argued that in his early reading of Nietzsche, Foucault elaborates the concept of tragic structure to give foundation, in epistemic sense, to the historical experiences of madness. Subsequently, we will trace the different formulations on tragic in Foucault’s early texts. The concept of tragic appears on these texts as a term to identify the negativity and of the oblivion in the field of the psychological knowledge. Finally, we will explain how Foucault re-elaborates Nietzsche’s concept of the tragic to expose an underlying determination to the history. The battle between the dionysian and apollonian elements defines the status of this experience.